Respuesta :

Answer:

[tex]x = 16[/tex]

Step-by-step explanation:

[tex] \frac{1}{2} (x + 8) - 16 = - 4[/tex]

[tex] \frac{1}{2} x + 4 - 16 = - 4[/tex]

[tex] \frac{1}{2} x + 4 = 12[/tex]

[tex] \frac{1}{2} x = 8[/tex]

[tex]x = 16[/tex]

Answer:

Step-by-step explanation:

[tex]\frac{1}{2}(x + 8 ) - 16 = - 4\\\\\frac{1}{2}*x + 8*\frac{1}{2} - 16 = -4\\\\\frac{1}{2}x + 4 - 16 = -4\\\\\frac{1}{2}x -12 = -4[/tex]

Add 12 to both sides

[tex]\frac{1}{2}x = -4 + 12\\\\\frac{1}{2}x = 8\\[/tex]

Multiply both sides by 2

[tex]x = 8*2\\\\x = 16[/tex]